PENGARUH REMINISCENCE THERAPY TERHADAP PENURUNAN TINGKAT DEPRESI PADA PASIEN DIABETES MELITUS DI UPT KESMAS GIANYAR I TAHUN 2019 - Ni Ketut Febriyanti; I Gusti HARINI; I Nengah Sumirta (Jurnal Gema Keperawatan, 2019)
The purpose of this study was to measure the level of depression before and after the treatment of reminiscence therapy and to analyze the impact of reminiscence therapy to depression on diabetes mellitus patients at Gianyar I Primary Health Center on 2019. The design of this study was pre experimental with one-group pre-post test design. The sample was taken by purposive sampling method with the number of 14 people. This research instrument uses Beck Depression Inventory II (BDI-II). The results showed that 14 subjects of depression before treatment were given most of them in the category of moderate depression as many as 9 people (64.30%) and after being treated mostly in the category of mild depression as many as 8 people (57,10%). Hypothesis test is done by using wilcoxon statistic with p value 0,001 (α = 0,05) can be interpreted there is significant influence of reminiscence therapy on decreasing levels of depression on diabetes mellitus patients at Gianyar I Primary Health Center on 2019, the conclutions of research is reminiscence therapy can decrease the level of depression in patients with diabetes mellitus.